Global strong solution of fourth order nonlinear wave equation. (August 2020) - Wang, Yitian; Liu, Shilong; Shao, Kun; Yang, Chao; Huang, Shaobin; Li, Wenke
Abstract: In this paper, we consider a class of fourth order nonlinear wave equation in a bounded domain with smooth boundary, and discuss the existence and uniqueness of the global strong solutions by gradually smoothing method.